Upaya Meningkatkan Kreativitas Mahasiswa PGMI STAI Sabilul Muttaqin dalam Menyajikan Mufrodat Bahasa Arab Melalui Aplikasi Canva - Khoirunnisa’il Fitriyah (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2023)
The aim of this research is to increase the creativity of PGMI STAI Sabilul Muttaqin Mojokerto students in designing attractive mufrodat using Canva media. This research method uses qualitative with descriptive research type. Types of data collection through observation, interviews and documentation. The data source in this research uses primary data; Madrasah Ibtidaiyah Teacher Education students at STAI Sabilul Muttaqin Mojokerto, while secondary data sources use; PGMI STAI Sabilul Muttaqin Mojokerto documents, books, relevant research journals. Data analysis techniques use the miles and Huberman models, namely; data collection, data reduction, data display, data verification, data conclusions and presentation of results. The results of this research are that PGMI STAI Sabilul Muttaqin Mojokerto students can increase their creativity in designing Arabic mufrodat using Canva media. Conduct further research to evaluate the effectiveness of using Canva in increasing creativity and learning Arabic, and compare it with other design methods.